Strategies for Healthy Eating Promotion and Behavioral Change Perceived as Effective by Nutrition Professionals: A Mixed-Methods Study - Mattei, Josiemer; Alfonso, Charmaine (Frontiers in Nutrition, 2020)
Nutrition professionals may recognize ways to improve diet among their clients/patients. This study aimed to survey strategies and foods that nutrition professionals in Puerto Rico perceive as most effective for healthy eating promotion and behavioral change. The study was a cross-sectional online mixed-methods survey conducted among registered members of the College of Nutritionists and Dietitians of Puerto Rico. Using close-ended questions, nutrition professionals identified foods that they considered as easy to include or difficult to control in the diet of their clients/patients, and strategies that may work best for healthy eating. Frequencies of responses were analyzed. Open-ended questions were qualitatively analyzed in NVivo v11. Response rate was 33.2% (n=414). The foods deemed as easy to include in the diet were root vegetables (66%), fruit (66%), legumes (57%), water (38%), and yogurt/dairy (37%). The foods deemed as more difficult to control were sugary beverages (63%), sweets and desserts (57%), fats and fried foods (56%), salt (50%), and white rice (44%). The strategies for healthy eating deemed effective were personalized orientation (79%), setting short-term goals (61%), making gradual dietary changes (53%), and setting health-oriented (41%) and personal (37%) goals. Emerging themes from qualitative analysis included the intuited key role of nutrition professionals, need for policy changes, emphasizing prevention, cultural sensitivity, and practical issues. Respondents suggested potential strategies across levels of the socioecological model. In conclusion, healthy eating strategies and foods perceived by nutrition professionals as effective may shape optimal nutritional counseling and population-wide approaches to improve healthy eating in Puerto Rico.